2004
DOI: 10.1103/physrevd.69.086002
|View full text |Cite
|
Sign up to set email alerts
|

Superstrings with intrinsic torsion

Abstract: We systematically analyse the necessary and sufficient conditions for the preservation of supersymmetry for bosonic geometries of the form Ê 1,9−d × M d , in the common NS-NS sector of type II string theory and also type I/heterotic string theory. The results are phrased in terms of the intrinsic torsion of G-structures and provide a comprehensive classification of static supersymmetric backgrounds in these theories. Generalised calibrations naturally appear since the geometries always admit NS or type I/heter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
755
0
11

Year Published

2004
2004
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(784 citation statements)
references
References 58 publications
18
755
0
11
Order By: Relevance
“…In all the known examples of IIB compactifications the resulting effective four-dimensional models were of no-scale type [8,19,23,25,31,35,38] and the overall size modulus remained free even after the introduction of fluxes. This cannot happen in the heterotic compactifications because of the modified Bianchi identity for the three-form [55,46]. As we will now show, the various terms appearing in equation (2.14) generically scale differently with respect to this parameter and therefore it needs to be fixed in order to obtain a consistent solution.…”
Section: The Superpotential and The Torsional Constraintsmentioning
confidence: 96%
See 2 more Smart Citations
“…In all the known examples of IIB compactifications the resulting effective four-dimensional models were of no-scale type [8,19,23,25,31,35,38] and the overall size modulus remained free even after the introduction of fluxes. This cannot happen in the heterotic compactifications because of the modified Bianchi identity for the three-form [55,46]. As we will now show, the various terms appearing in equation (2.14) generically scale differently with respect to this parameter and therefore it needs to be fixed in order to obtain a consistent solution.…”
Section: The Superpotential and The Torsional Constraintsmentioning
confidence: 96%
“…An interesting subclass of solutions of the geometrical constraints (2.8)-(2.10) is given by manifolds which are products of tori and twisted tori (included in the class of the nilmanifolds in [37]) or by torus fibration of Calabi-Yau two-folds, where the fiber is twisted [33,37,42,45,46,52]. A simple instance of such spaces is given by a metric of the form…”
Section: The Superpotential and The Torsional Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global symmetries which do not act on the supercharge are called flavor symmetries, and they are divided into two groups, mesonic and baryonic symmetries. 2 These global symmetries should be realized as gauge symmetries in string theory. The purpose of this section is to identify the gauge symmetries corresponding to the global symmetries in gauge theories.…”
Section: Global Symmetriesmentioning
confidence: 99%
“…This duality has been generalized to more complicated ones. The recent discovery of the explicit metrics of classes of Sasaki-Einstein manifolds [2,3,4] provides us many examples of dualities we can explicitly check the validity. For example, it has been confirmed that the volumes of the SasakiEinstein manifolds and some supersymmetric cycles in them correctly reproduce the central charges and conformal dimensions of baryonic operators in superconformal gauge theories, which can be determined on the field theory side with the help of the a-maximization technique [5].…”
Section: Introductionmentioning
confidence: 99%